Iatrogenic pneumothorax in dog after attempt to cardiopulmonary resuscitation (CPR) - Rodrigues, F. R. N.; Matos, M. G.; Lopes, C. E. B.; Pimentel, S. P.; Viana, D. A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Pneumothorax is the presence of air in the pleural cavity resulting from a discontinuity of the pleural membrane, which allows air to enter the thoracic environment, turning positive the pressure that was negative (ARRUDA, 2011). This condition can surge by spontaneous, traumatic or iatrogenic way. It can be classified as open or closed pneumothorax. The former is produced by a penetrating trauma generating a communication between the thoracic cavity and outer environment turning possible the progressive air penetration. The latter is caused by a blunt trauma and the air accumulation occurs due to extravasation from the injured lung parenchyma, bronchial tree, trachea or esophagus. The consequence of the intrathoracic positive pressure involves: decreased venous return, decreased cardiac output and progressive respiratory insufficiency, possibly resulting in rapidly patient’s death. This paper is a report of an iatrogenic pneumothorax case confirmed by a necropsy exam (ANDRADE FILHO; CAMPOS; HADDAD, 2006).